Black Myth: Wukong – The Internationalization of Chinese Games - Meng, Qianwen (Journal of Modern Social Sciences, 2025)
This study focuses on the globalization pathway of the Chinese game Black Myth: Wukong, exploring how it achieves the global dissemination of traditional Chinese culture and commercial success through the modern gaming industry. Using a case study approach and combining qualitative and quantitative data, this research comprehensively analyzes the entire process of Black Myth: Wukong from its development in 2020 to its global release in 2024, with a particular emphasis on how its technological innovation, cultural symbol reconstruction, and cross-cultural communication strategies have driven its success in the international market. The study reveals that Black Myth: Wukong employs advanced gaming technologies such as Unreal Engine 5 and ray tracing, which not only achieve breakthroughs in visual and interactive experiences but also bridge the gap between Chinese culture and global players through the modern reinterpretation of cultural symbols (e.g., Sun Wukong, demons, and monsters). The game has sold over 20 million copies worldwide, generating total revenues exceeding 961 million, making it a benchmark case for the internationalization of the Chinese gaming industry. Furthermore, the research highlights the core challenges of cross-cultural communication, including differences in cultural background understanding and the diversity of symbol reception. It proposes strategies such as localization adjustments and cultural re-creation to address these challenges. Additionally, the study summarizes key success factors for Chinese cultural products in the global commercial market, including the integration of cultural innovation, technological support, and marketing strategies.